MÁXIMA EFICIÊNCIA TÉCNICA E ECONÔMICA DA APLICAÇÃO DE PENERGETIC® NA CULTURA DO ALGODOEIRO - LOPES, Fernando de Souza; COSTA, Victor Souza; GREITER, Luiz Mateus Gonçalves; MALDONADO, Eduardo da Cunha; SILVA, Pablo Rozo; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-